The Ashford affair - Willig, Lauren (St. Martin's Press, 2013)
Feeling unfulfilled in the face of an imminent legal partnership and a broken engagement, Manhattan lawyer Clementine Evans learns of a long-buried family secret that leads her to the inner circles of World War I British society and the red hills of Kenya.